Alterações comportamentais e neuroquímicas causadas por compostos orgânicos de selênio - Ghisleni, Gabriele Cordenonzi (2006)
Selenium organic compounds, ebselen and diphenyl diselenide (PhSe)2, are considered mimics of glutathione peroxidase enzyme and present antioxidants and anti-inflammatory properties in different models of brain injury. In view of the pharmacological actions of (PhSe)2 seem to be more potent than its analogue ebselen, this study was delineated to evaluate the effect of this compound on cell death and in immunocontent detection of inducible nitric oxide sinthase, in a model of oxygen and glucose deprivation in rat hippocampal slices. We observed that the neuroprotection action of (PhSe)2 was correlated with the suppression on immunocontent of inducible nitric oxide sinthase enzyme. The neuroprotection action of (PhSe)2 was dose dependent and more pronunciated than its equivalent compound previously described ebselen. Since both compounds, ebselen and (PhSe)2, are able to modulate some parameters of glutamatergic system in vivo and in vitro, and the compound ebselen presented neuroprotective effect in a model of glutamate toxicity following redution on lipid peroxidation, we also evaluated in this work, the effect of these compounds on increase of ectonucleotidases activities induced by glutamate in rat cultived cerebellar cells. It was observed that both selenium compounds did not modify the ectonucleotidases activities, but prevent glutamate stimulation on ATP and AMP hydrolysis. In the attempt of correlate the preventive effect of these compounds with their antioxidant activity, we compared the effect of trolox, a classic antioxidant described in literature. Trolox, similarly to selenium compounds, also prevent the increase on ectonucleotidases atictivities induced by glutamate. Although glutamate did not unchain cell death after 24 hours of previous cells exposure to glutamate, it was suggested that part of ebselen and (PhSe)2 action can be related to their antioxidants properties. It was still inferred that the participation of sulfhidril groups on selenium compounds effects seems to be involved on their neuroprotective effects, a time that as much the increase on nucleotides hydrolysis as the neuronal death for alkylant agent NEM were prevented by both compounds. Co-incubation of NEM and glutamate did not modify the profile of cell death and nucleotides hydrolysis stimulation, with ebselen and (PhSe)2 partially reverting the increase on ATP hydrolysis and cell death. However, both compounds were ineffective in revert the increase on AMP hydrolysis caused by co-incubation of NEM and glutamate. Although both compounds partially prevent cell death evidenced by co-incubation of these two citotoxics agents, the action of ebselen and (PhSe)2 seems differently modulate these enzymes. Through behavioral studies with intraperitoneal administration of (PhSe)2, we observed that (PhSe)2 did not alter the exploratory activity of animals when evaluated on open field task. However, in this task, animals administered with 50 μmol/kg of (PhSe)2 presented decreased number of defecations, a behavior that correspond at a first index of diminish intrinsic anxiety in animals displayed for a new environment. From these observations, the higher dose of (PhSe)2 was not used in the experiments where consolidation memory of animals was evaluated. On the inhibitory avoidance task animals treated with 25 μmol/kg of (PhSe)2 had a diminished performance only for consolidation of short-term memory, therefore this supposed amnesic effect was not observed on consolidation of long-term memory. Although the results found on inhibitory avoidance task, the mechanisms involved on amnesic effect of (PhSe)2 were not explored. From the diminished number of defecations on open field task, the animals were treated with 50 μmol/kg of (PhSe)2 and submitted to elevated plus maze task for better characterize a possible anxiolytic effect. It was possible to observe that animals treated with the dose of 50 μmol/kg, presented less anxious behavior for the higher permanency on open arms and for the increase on number of entries in open arms. This effect was similar with classical pharmacological drugs with anxiolytic action as diazepam. Thus, the participation of other neurotransmitter systems was investigated on anxiolytic effects of (PhSe)2 for administration of agonists and antagonists of GABAergic and serotoninergic system. A time that antagonists for GABAA and 5-HT2A/C receptors reverted the anxiolytic action of (PhSe)2, we suggest that both classical neurotransmitter systems involved on anxiolytic/anxiogenic behavior participate of anxiolytic effect of this compound.